2013
DOI: 10.1371/journal.pone.0054968
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator Activated Receptor-α/Hypoxia Inducible Factor-1α Interplay Sustains Carbonic Anhydrase IX and Apoliprotein E Expression in Breast Cancer Stem Cells

Abstract: AimsCancer stem cell biology is tightly connected to the regulation of the pro-inflammatory cytokine network. The concept of cancer stem cells “inflammatory addiction” leads to envisage the potential role of anti-inflammatory molecules as new anti-cancer targets. Here we report on the relationship between nuclear receptors activity and the modulation of the pro-inflammatory phenotype in breast cancer stem cells.MethodsBreast cancer stem cells were expanded as mammospheres from normal and tumor human breast tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 58 publications
1
48
0
1
Order By: Relevance
“…However, our results indicate that this gene mRNA expression could be reversed by MK886 treatment. The ability of MK886 to decrease the expression of VEGF has been previously reported in a study on human pancreatic cancer cells (Zhou et al 2011), whereas a recent study conducted by Papi et al (2013) showed that PPARa and HIF1a have functional interplays in which their expressions are enhanced by each other, resulting in pro-inflammatory responses. This would support the current finding that HIF1a positively correlates with the expression of PPARa.…”
Section: Discussionmentioning
confidence: 72%
“…However, our results indicate that this gene mRNA expression could be reversed by MK886 treatment. The ability of MK886 to decrease the expression of VEGF has been previously reported in a study on human pancreatic cancer cells (Zhou et al 2011), whereas a recent study conducted by Papi et al (2013) showed that PPARa and HIF1a have functional interplays in which their expressions are enhanced by each other, resulting in pro-inflammatory responses. This would support the current finding that HIF1a positively correlates with the expression of PPARa.…”
Section: Discussionmentioning
confidence: 72%
“…It has been proposed that "NF-kB activity addiction" would make CSCs more susceptible to NF-kB inhibitors than their normal counterparts [26,55] . For these reasons the use of molecules, as NRs ligands, capable of inhibiting NF-kB dependent inflammation may be the best strategy to hamper BCSCs growth [74,86] . Recently, we demonstrated that BCSCs have a particular NRs phenotype [86,87] (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…For these reasons the use of molecules, as NRs ligands, capable of inhibiting NF-kB dependent inflammation may be the best strategy to hamper BCSCs growth [74,86] . Recently, we demonstrated that BCSCs have a particular NRs phenotype [86,87] (Figure 1). Therefore, the synergic use of multiple molecules (as ligands of NRs) at lower doses might be a good strategy to kill BCSCs, while inducing fewer side effects in patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that p66Shc/Notch-3 interplay modulates self-renewal (by inducing Notch-ligand Jagged-1) and hypoxia survival (by inducing CA9) in mammary gland stem/progenitor cells (Sansone et al 2007a, b). They also recently demonstrated that the peroxisome proliferator-activated receptor-α/hypoxia inducible factor-1α (PPAR-α/HIF-1α) interplay induces the expression of CA9 along with interleukin-6 (IL-6) and apolipoprotein E (Papi et al 2013). …”
Section: Transcriptional Regulation Of the Ca9 Genementioning
confidence: 99%